Analisis Faktor-Faktor Yang Mempengaruhi Keterlambatan Proyek Apartemen Opus Bay Balmoral Batam - Iswanda, Dyo; Hudori, Mahfuz (Jurnal Ilmiah Rekayasa Sipil, 2023)
Currently construction projects in Batam City in the field of foundations are increasing rapidly. This is a factor of success and economic growth in Batam City. The city of Batam has shown several towering construction buildings. Tall buildings are very easy to find in Batam City today. The increasing construction of high-rise buildings in Batam City must also be in line with the increase in the success of the project so that construction projects must be completed according to the specified schedule, the right budget, such as making a budget plan, and the expected final results. This study aims to identify the factors that cause delays in the Opus Bay Balmoral project in Batam City. Collecting data in this study used a survey method with a questionnaire instrument and direct interviews with respondents. Data were analyzed using the Relative Score Index method to obtain information on the dominant factors causing delays in the Opus Bay Balmoral development project in Batam City. The research results obtained, there are three factors which indicate that the factors causing the delay in the Opus Bay Balmoral project are: weather factors, design factors, and location factors. These three factors have relative index scores of 0.791, 0.508, and 0.505. Because these three factors have a Relative Index value of > 0.5, with a value for the design factor itself of 0.508, for the weather factor of 0.719 and a location factor of 0.505.